Qualitative Meta-Analysis: The Effectiveness Of Video Games In Second Language Acquisition - Soeprianto Wibowo, La Ode Andi; Hana, Haerun; Sartiah, Sartiah (Halu Oleo University, 2018)
The use of Computer Assisted Language Learning (CALL) in improving the capacity of language learners both for children and adults has been proved for the last decades. Each year new media has been designed to balance the development of technology especially in language educational aspect. The use of video games as the media in educational aspect has been started in 1970 and since then it keeps growing. Recent years, the appearing of video games in language learning and acquisition has been monitored. Though there was research that revealed some bad effects of video games for children, it was only applied for children that have no control over their game playing time. Also, it is not wise to look at negative effect of video games while we do not concern of its’ good effect. The objective of this study is to explore the effectiveness of the research that used video games as its media to improve the language proficiency and skill of the participants. By listing out the characteristic of each subject of research, it is then analyzed based on what ways the video games affected the language proficiency of the participants and the effectiveness of the video games used in the research. Then, it is concluded to the facilitative features of the video games toward language acquisition based on the result of analysis. In the end, the limitations of the study are listed and also recommendations for future studies related to the use of video games in language learning and acquisition are presented.